2015
DOI: 10.1007/s11881-015-0115-x
|View full text |Cite|
|
Sign up to set email alerts
|

Preservice teacher knowledge of basic language constructs in Canada, England, New Zealand, and the USA

Abstract: The present study examined preservice teachers' (PSTs) knowledge of basic language constructs across four different English-speaking teacher preparations programs. A standardized survey was administered to participants from Canada (n = 80), England (n = 55), New Zealand (n = 26), and the USA (n = 118). All participants were enrolled in undergraduate university programs that led to teacher certification for general education in the primary grades. Our data reveal that preservice teachers from all four countries… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
38
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 45 publications
7
38
0
1
Order By: Relevance
“…A growing number of studies provide descriptions of educators' knowledge to support language and literacy (e.g., Bos, Mather, Dickson, Podhajski, & Chard, ; Cunningham et al, ; Moats, ; Moats & Foorman, ; Moats & Lyon, ; Phelps, ; Puliatte & Ehri, ; Spear‐Swerling, Brucker, & Alfano, ; Washburn, Binks‐Cantrell, Joshi, Martin‐Chang, & Arrow, ; Washburn, Joshi, & Binks‐Cantrell, ). Typically, these studies characterize educators' knowledge as less than optimal.…”
Section: Educators' Knowledge To Support Early Language and Literacy mentioning
confidence: 99%
“…A growing number of studies provide descriptions of educators' knowledge to support language and literacy (e.g., Bos, Mather, Dickson, Podhajski, & Chard, ; Cunningham et al, ; Moats, ; Moats & Foorman, ; Moats & Lyon, ; Phelps, ; Puliatte & Ehri, ; Spear‐Swerling, Brucker, & Alfano, ; Washburn, Binks‐Cantrell, Joshi, Martin‐Chang, & Arrow, ; Washburn, Joshi, & Binks‐Cantrell, ). Typically, these studies characterize educators' knowledge as less than optimal.…”
Section: Educators' Knowledge To Support Early Language and Literacy mentioning
confidence: 99%
“…These findings were similar to the study by Washburn et al [6] and Moats [39], who also found that teachers had great difficulty with various aspects of morphology. This could be due to the general lack of emphasis on systematic classroom instruction on morphological structure of words [40], especially in beginning reading instructions [41]. Moreover, it has been widely established that phonological processing deficit is the cause of the difficulty faced by struggling readers [40], and that phonological awareness helps students in letter-to-sound correspondences while morphological awareness helps in the reading of more complex words, after decoding abilities have been acquired [34].…”
Section: Morphologymentioning
confidence: 99%
“…For many years, some researchers focused on the discussion that teachers' content knowledge impacts students' achievement. Those studies found that the lack of teachers' knowledge should find the difficulties of the teaching-learning process [21], [22], [23], [24]. Darling Hammond stated that teachers' content knowledge is the fundamental requirement for an effective teaching [25].…”
Section: Content Knowledge (Ck)mentioning
confidence: 99%
“…It found that a reading progress at the school could be the failure with the lack of an effective teaching [26]. The study was focused on the reading for learners with dyslexia.…”
Section: Content Knowledge (Ck)mentioning
confidence: 99%